The Effect of the Contextual Teaching and Learning (CTL) Learning Model Assisted by Learning Video Media on the Economic Learning Outcomes of Class XI IPS Students of SMA Negeri 1 Completed T.A 2022/2023 - Renny Juliadi; Putri Kemala Dewi Lubis (Indonesian Journal of Advanced Research, 2023)
This study aims to determine differences in students' economic learning outcomes using the Contextual Teaching and Learning (CTL) learning model assisted by learning video media compared to using conventional learning models in class XI IPS at SMA Negeri 1 Completed Academic Year 2022/2023. The population in this study were 141 students in class XI IPS, while the sample in class XI IPS 3 and 4 was 69 students. The results of the research show that the post test significance value for the experimental and control classes is 0.0035 <0.05, so Ho is rejected. This means that there is a significant difference in student economics learning outcomes that are higher by using the Contextual Teaching and Learning (CTL) learning model assisted by learning video media compared to using conventional learning models in class XI IPS SMA Negeri 1 Completed Academic Year 2022/2023. So, it can be concluded that the Contextual Teaching and Learning (CTL) learning model assisted by learning video media has an effect on the economics learning outcomes of class XI IPS students of SMA Negeri 1 Completed T.A 2022/2023.